Sustainable Development and the Farm Accountancy Data Network (FADN) - Machnacki, Mirosław; Kondraszuk, Tomasz (Zrównoważony rozwój a system zbierania danych rachunkowych z gospodarstw rolniczych (FADN), 2011)
This article aims to present the state of research on sustainable development of agriculture on the basis of studies of relevant literature. The first stage of the study involved the analysis of the idea of sustainable agriculture and its impact on agricultural policy. The next step was to analyze instruments supporting sustainable development of farms and to undertake an assessment and measure agricultural holdings as regards their degree of sustainability. Commercial records should constitute the source for this data. Accounting in the case of farming provides wealth of information useful for assessing the impact of farms on the environment because agricultural production processes involve various elements of the environment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 79-86
Keywords: sustainable development; farm; agricultural holding; cost accounting; accounting